2021
DOI: 10.1111/jvh.13606
|View full text |Cite
|
Sign up to set email alerts
|

Baseline HBV‐DNA load plus AST/ALT ratio predicts prognosis of HBV‐related hepatocellular carcinoma after hepatectomy: A multicentre study

Abstract: Hepatitis B viral (HBV) load and hepatic enzymes play a critical role in hepatocellular carcinoma (HCC) development. However, the clinical significance of these in HBV‐related HCC patients after hepatectomy remains unclear. In this study, we analysed 1,940 HBV‐related HCC patients who underwent hepatectomy from four hospitals in west China. Risk classification was constructed based on baseline HBV‐DNA load and AST/ALT ratio. Based on the HBV‐DNA load and AST/ALT ratio classification, four types with distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
1
9
1
Order By: Relevance
“…Since Fernando De Ritis first described AST/ALT ratio as an enzymatic test for viral hepatitis in 1957 [ 14 ], researchers have taken it as a potential prognostic biomarker in various diseases [ 8 13 , 15 , 16 ]. Also, Granito et al [ 17 ] evaluated the prognostic significance of changes in liver parameters as predictors of treatment response to cTACE.…”
Section: Discussionmentioning
confidence: 99%
“…Since Fernando De Ritis first described AST/ALT ratio as an enzymatic test for viral hepatitis in 1957 [ 14 ], researchers have taken it as a potential prognostic biomarker in various diseases [ 8 13 , 15 , 16 ]. Also, Granito et al [ 17 ] evaluated the prognostic significance of changes in liver parameters as predictors of treatment response to cTACE.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous experience, the decreased ALB, increased LDH or increased NLR has been proved to be independent negative prognostic factors for OS ( Arkenau et al, 2008 ; Bigot et al, 2017 ). The AST-to-ALT ratio was reported to stratify HBV-related HCC patients with distinguishable prognosis effectively after hepatectomy ( Shen et al, 2021 ). And the TBIL was also found as a prognostic factor for OS in terms of HCC patients previously ( Yang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason might be detectable HBV DNA per se promote tumour cell growth. Studies reported that preoperative serum HBV DNA and Ishak hepatic inflammation score are risk factors for HCC recurrence after hepatectomy [ 4 , 6 , 7 ]. We found that hepatic inflammation was not a risk factor for HCC recurrence because patients had a normal liver function after OLT.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, the most common aetiology of HCC is CHB infection. A serum hepatitis B virus DNA (HBV DNA) level is correlated with the risk of HCC [ 2 , 4 , 5 ], and serum HBV DNA detectable and HBV DNA >2000 IU/mL are risk factors for HCC recurrence after hepatectomy [ 4 , 6 , 7 ]. Whether preoperative HBV DNA status is a risk for HCC recurrence after OLT is unclear, therefore, we recruited patients with HCC who had OLT from a referral medical centre and explored risk factors for HCC recurrence and characteristics of patients with HCC and detectable HBV DNA.…”
Section: Introductionmentioning
confidence: 99%